Sifat Campuran Herbisida Berbahan Aktif Bentazon dan MCPA Terhadap Gulma Daun Lebar, Teki dan Rumput - Uum Umiyati; Dedi Widayat; Dani Riswandi; Reza Amalia (Universitas Sebelas Maret, 2021)
Weed control using a single herbicide with same active ingredients can add the risk of weed resistance. Using mixed herbicides can increase the spectrum of weeds controlled, and inhibit weed resistance. Herbicide mixture with two or more types of active ingredients will show the interactions between one and another ingredient. These interactions could be synergistic, antagonistic, and additive. The research was to determine the response of mixed herbicide Bentazon, MCPA 460 g. L⁻¹ and their mixed characteristic. This experiment was conducted from June until August 2019 in the greenhouse at the Faculty of Agriculture, Universitas Padjadjaran. The treatment consisted of three types of herbicides with six dose levels, namely a single herbicide of Bentazon 400 g. L⁻¹ and MCPA 60 g. L⁻¹ (4; 2; 1; 0.5; 0.25; 0 L.ha⁻¹), a mixed herbicide Bentazon MCPA 460 g.L⁻¹ (5; 2.5; 1.25; 0.625; 0.3215; 0 L.ha⁻¹) with four replications. The target weeds tested were Spenochlea zeylanica, Ludwigia hyssopifolia, Fimbristylis miliacea, and Cyperus iria was taken from the Ciparay area. Data were analysed by linear regression analysis and multiplicative survival model (MSM) method to determine the LD50 treatment and expectation. The result showed that compound herbicides of Bentazon and MCPA LD50 treatment (0,3857 g.ha⁻¹) had smaller value than LD50 expectation (0,6943 g.ha⁻¹) with a ecotoxicity value of 1.8 (> 1), so that the herbicide mixture was synergistic.